Evidence for major structural changes in subunit C of the vacuolar ATPase due to nucleotide binding - Armbrüster, Andrea; Schumacher, Karin (FEBS letters, 2005)
The ability of subunit C of eukaryotic V-ATPases to bind ADP and ATP is demonstrated by photoaffinity labeling and fluorescence correlation spectroscopy (FCS). Quantitation of the photoaffinity and the FCS data indicate that the ATP-analogues bind more weakly to subunit C than the ADP-analogues. Site-directed mutagenesis and N-terminal sequencing of subunit C from Arabidopsis (VHA-C) and yeast (Vma5p) have been used to map the C-terminal region of subunit C as the nucleotide-binding site. Tryptophan fluorescence quenching and decreased susceptibility to tryptic digestion of subunit C after binding of different nucleotides provides evidence for structural changes in this subunit caused by nucleotide-binding.